Escenas de sororidad: teatro, performance y redes de mujeres en la prensa brasileña - María Alejandra Aguilar Dornelles (Les Cahiers ALHIM)
This essay explores the presence of Cancros sociais (1865), by Maria Angélica Ribeiro (1829-1880) in Rio de Janeiro’s press, focusing particularly on the indications of the existence of a network of women linked to theatre and literature. In a period marked by the suspicion of the figure of the “literata” and strong opposition to women's right to education, Cancros sociais constitutes a fundamental case to understand women’s success. Particularly, I explore a tribute to Ribeiro starring a group of women who staged her support and publicly celebrated her as the greatest playwright of the period. The spectacularization of women’s solidarity reveals that the theatre contributed to the circulation of gender performances that questioned patriarchy. Thus, the press not only shows how journalists and editors took advantage of the emergence of a public consuming works written by women, but also offer us a broader vision of the role of theatre as a platform for making visible practices of sisterhood and empowerment.